Inflammatory Myofibroblastic Tumor (Inflammatory Pseudotumor) of the Pelvis. - Piñeyro, Alberto; Derboghosian, Alejandro (Cirugía del Uruguay, 2003)
An infrequent clinical case of pelvic myofibroblastic inflammatory tumor was initially diagnosed as Malignant Fibrous Histiocytoma. Even though not all agree, sorne facts appear to support the hypothesis that is a genuine neoplasia. Its course is generally benign, local recurrence rare and its malignant transformation exceptional